2011
DOI: 10.1073/pnas.1110118108
|View full text |Cite
|
Sign up to set email alerts
|

Structural reorganization of the antigen-binding groove of human CD1b for presentation of mycobacterial sulfoglycolipids

Abstract: The mechanisms permitting nonpolymorphic CD1 molecules to present lipid antigens that differ considerably in polar head and aliphatic tails remain elusive. It is also unclear why hydrophobic motifs in the aliphatic tails of some antigens, which presumably embed inside CD1 pockets, contribute to determinants for T-cell recognition. The 1.9-Å crystal structure of an active complex of CD1b and a mycobacterial diacylsulfoglycolipid presented here provides some clues. Upon antigen binding, endogenous spacers of CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…Studies performed with recombinant soluble proteins revealed that CD1b, CD1c and CD1d are associated with different lipids [11][12][13][14][15][16][17], suggesting that CD1 molecules are not assembled with empty pockets (Table 1). Thus, lipids bound by CD1 during assembly in the ER might contribute to stabilisation of assembled molecules, resembling the binding of peptides to nascent MHC class I molecules …”
Section: Extracellular Antigen Transport and Uptakementioning
confidence: 96%
See 2 more Smart Citations
“…Studies performed with recombinant soluble proteins revealed that CD1b, CD1c and CD1d are associated with different lipids [11][12][13][14][15][16][17], suggesting that CD1 molecules are not assembled with empty pockets (Table 1). Thus, lipids bound by CD1 during assembly in the ER might contribute to stabilisation of assembled molecules, resembling the binding of peptides to nascent MHC class I molecules …”
Section: Extracellular Antigen Transport and Uptakementioning
confidence: 96%
“…During loading with a well characterised antigenic sulfoglycolipid, CD1b undergoes a conformational change in the key residues, glutamic acid at position 80 and tyrosine at position 151, which approximate, thus closing the F 0 pocket. Lipid-antigen loading also induces a sliding of the spacer, which assumes a novel position and moves towards the A 0 pocket [16]. Importantly, spacers with different length can associate with CD1b, thereby lipid antigens with different alkyl chains can be optimally accommodated.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lipids might contribute in an indirect way to TCR activation even in the absence of TCR contact. Lipids can alter the surface of the CD1 protein by pushing outward on key residues or closing up loose ternary structures (Garcia-Alles et al 2006; McCarthy et al 2007; Garcia-Alles et al 2011; Mansour et al 2016). …”
Section: An Alternate Model: Absence Of Interferencementioning
confidence: 99%
“…To investigate how the natural product 1 might be bound by CD1b, the CD1b-diacylsulfoglycolipid co-crystal structure (PDB code: 3T8X) 46 was used as a template to model the natural product into the deep binding pocket. 1 was manually docked into the binding groove, and the energy of the system minimized using the MAB force eld as implemented in the computer program MOLOC, 47 while keeping the protein coordinates xed.…”
Section: Modeling Studiesmentioning
confidence: 99%